The Use of a Nonprobability Internet Panel to Monitor Sexual and Reproductive Health in the General Population. (March 2018) - Legleye, Stéphane; Charrance, Géraldine; Razafindratsima, Nicolas; Bajos, Nathalie; Bohet, Aline; Moreau, Caroline; ,
Background: Reliability of nonprobability online volunteer panels for epidemiological purposes has rarely been studied. Objectives: To assess the quality of a questionnaire on sexual and reproductive health (SRH) administered in a nonprobability Web panel and in a random telephone survey ( n = 8, 992; n = 8, 437, age 16–49 years). Especially, we were interested in the possible difference in the association of sociodemographic variables and some outcome variables in the two surveys that are in the reliability of analytical epidemiological studies conducted in such panels. Methods: Interventions to increase response rate were used in both surveys (four e-mail reminders, high number of call attempts and callbacks to refusals). Both were calibrated on the census population. Sociodemographic composition, effects of reminders, and prevalence were compared to their telephone counterpart. In addition, the associations of sociodemographic and sexual behaviors were compared in the two samples in multivariate logistic regressions. Results: The online survey had a lower response rate (20.0 percent vs. 44.8 percent) and a more distorted sociodemographic structure although the reminders improved the representativeness as did the analogous interventions on the telephone survey. Prevalences of SRH variables were similar for the common behaviors but higher online for the stigmatized behaviors, depending on gender. Overall, 29 percent of the 63 interactions studied were significant for males and 11 percent for women, although opposite effects of sociodemographic variables were rare (5 percent of the 171 tested for each gender). Conclusion: Nonprobability online panels are to be used with caution to monitor SRH and conduct analytical epidemiological studies, especially among men.